Regional Specialisation and Economic Concentration in Romania - Neagu, Olimpia; Neagu, Madalin Ioan (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The purpose of the paper is to give an overview of the changes in the structure of industries in Romania, specifically on the questions (1) whether the industrial structures become more similar or more different in the Romanian regions and (2) whether the Romanian industries become more concentrated or more dispersed. EUROSTAT regional data on Gross Value Added and employed population for the period of 2000-2013 are used in order to calculate several statistical indices of specialization and concentration (Krugman, Entropy, Hirschman-Herfindahl, Lilien Index and Gini coefficient). By comparing the values of these different measurements, the main finding is that Romanian regions become less specialized, while industries become slightly more concentrated. The speed of structural changes in all Romanian regions registered a noticeable slowdown of the speed of sectoral changes after the economic crisis. Our conclusions provide useful information for the economic policy makers in investment funds allocation or employment measures designing.